All Questions Topic List
None Questions
Previous in All Question Next in All Question
Previous in None Next in None
Question Number 122406 by mathdave last updated on 16/Nov/20
solve∫0π4ln(tan2x+2)dx
Answered by TANMAY PANACEA last updated on 16/Nov/20
f(x)=ln(2+tan2x)f(0)=ln2f(π4)=ln3∫0π4ln3dx>∫0π4f(x)dx>∫0π4lm2dxπ4ln3>I>π4ln2
Answered by mathmax by abdo last updated on 16/Nov/20
I=∫0π4ln(1+tan2x+1)=∫0π4ln(1+1cos2x)dx=∫0π4ln(1+cos2x)dx−2∫0π4ln(cosx)dx∫0π4ln(1+cos2x)dx=∫0π4ln(1+1+cos(2x)2)dx=∫0π4ln(3+cos(2x))dx−π4ln(2)=π4ln(3)+∫0π4ln(1+13cos(2x))dx−π4ln(2)∫0π4ln(1+13cos(2x))dx=2x=t12∫0π2ln(1+13cost)dtletf(a)=∫0π2ln(1+acost)dtwith0<a<1f′(a)=∫0π2cost1+acostdt=1a∫0π21+acost−11+acostdt=π2a−1a∫0π2dt1+acost(→tan(t2)=u)=π2a−1a∫012du(1+u2)(1+a1−u21+u2)=π2a−2a∫01du1+u2+a−au2=π2a−2a∫01du1+a+(1−a)u2wehave2a∫01du1+a+(1−a)u2=2a(1+a)∫01du1+1−a1+au2=1−a1+au=z2a(1+a)∫01−a1+a11+z2×1+a1−adz=2a1−a2arctan(1−a1+a)⇒f(a)=π2lna−2∫arctan(1−a1+a)a1−a2da+c∫arctan(1−a1+a)a1−a2da=a=cosθ∫arctan(tan(θ2))cosθ.sinθsinθdθ=12∫θcosθdθ.....becontinued....
Terms of Service
Privacy Policy
Contact: info@tinkutara.com